Research on 5G-R Modulation Interference Performance in Agricultural and Forestry Environment - Zhukai Shen, Jinbai Zou, Aihuang Guo, Lidong Zhang (Forest Chemicals Review, 1970)
With the development of new services and new requirements of railway 5G special mobile communication network, a large number of communication equipment along the railway will be placed in a large area of agroforestry environment, and will inevitably be interfered by different modulation signals in different wireless communication systems. Therefore, it is of great significance to study the interference between different modulation signals. In this paper, the communication scene was firstly abstracted, a QAM demodulation model was established, and the error rate of 5G-R 64QAM modulation signal under additive White Gaussian noise (AWGN) was calculated by monte Carlo method. Secondly, the bit error rate formula of M-QAM under two-dimensional digital modulation interference was derived, and the influence of phase difference on interference performance was analyzed. Finally, the model simulation of 5G-R 64QAM system was carried out, and the influence of different M-QAM modulation signals on 64QAM demodulation was compared. The simulation results showed that quadrature phase shift keying (QPSK) has great influence on 64QAM demodulation performance, and different phase shifts have little influence on bit error rate. The conclusion of this study can provide theoretical support for the anti-interference performance of communication equipment along the line in agricultural and forestry environment, and has practical engineering value.